2020
DOI: 10.1007/s11222-020-09931-z
|View full text |Cite
|
Sign up to set email alerts
|

Variance reduction for Markov chains with application to MCMC

Abstract: In this paper we propose a novel variance reduction approach for additive functionals of Markov chains based on minimization of an estimate for the asymptotic variance of these functionals over suitable classes of control variates. A distinctive feature of the proposed approach is its ability to significantly reduce the overall finite sample variance. This feature is theoretically demonstrated by means of a deep non asymptotic analysis of a variance reduced functional as well as by a thorough simulation study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…A control variate g should therefore be selected such that π ( g )=0 and σ ( h − g )≪ σ ( h ). In inequality (3.2) it was demonstrated that, in the large m and k limit, the quantity σ ( h ) 2 is just the asymptotic variance from traditional MCMC sampling; existing gradient‐based control variates can therefore be used (Belomestny et al ., ; Mijatović and Vogrinc, ). However, at finite m and k the dependence of σ ( h ) on h is far from explicit.…”
Section: Discussion On the Paper By Jacob O’leary And Atchadémentioning
confidence: 98%
“…A control variate g should therefore be selected such that π ( g )=0 and σ ( h − g )≪ σ ( h ). In inequality (3.2) it was demonstrated that, in the large m and k limit, the quantity σ ( h ) 2 is just the asymptotic variance from traditional MCMC sampling; existing gradient‐based control variates can therefore be used (Belomestny et al ., ; Mijatović and Vogrinc, ). However, at finite m and k the dependence of σ ( h ) on h is far from explicit.…”
Section: Discussion On the Paper By Jacob O’leary And Atchadémentioning
confidence: 98%
“…The main challenge in developing control variates, or functionals, based on Stein operators is therefore to find a function g n such that the asymptotic variance σ(f − f n ) 2 is small. To explicitly minimize asymptotic variance, Mijatović & Vogrinc (2018); Belomestny et al (2020) and Brosse et al (2019) restricted attention to particular Metropolis-Hastings or Langevin samplers for which asymptotic variance can be explicitly characterized. The minimization of empirical variance has also been proposed and studied in the case where samples are independent (Belomestny et al, 2017) and dependent (Belomestny et al, 2020(Belomestny et al, , 2019.…”
Section: Stein Operatorsmentioning
confidence: 99%
“…To explicitly minimize asymptotic variance, Mijatović & Vogrinc (2018); Belomestny et al (2020) and Brosse et al (2019) restricted attention to particular Metropolis-Hastings or Langevin samplers for which asymptotic variance can be explicitly characterized. The minimization of empirical variance has also been proposed and studied in the case where samples are independent (Belomestny et al, 2017) and dependent (Belomestny et al, 2020(Belomestny et al, , 2019. For an approach that is not tied to a particular Markov kernel, authors such as Assaraf & Caffarel (1999) and Mira et al (2013) proposed to minimize mean squared error along the sample path, which corresponds to the case of an independent sampling method.…”
Section: Stein Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent promising examples of such endeavours include new strategies for the determination of generic observables [9][10][11] and transport properties [12][13][14] , as well as force-based estimators to sample local properties such as number, charge and polarization densities, radial distribution functions (RDF) or local transport properties with a reduced variance 10,11,[15][16][17][18][19][20][21] . The availability of different estimators for the same observable opens the possibility of exploiting another well known approach to further reduce the variance, namely the control variates method [22][23][24][25][26][27][28][29][30] . Here we show the potential of combining of estimators for the determination of RDF and onedimensional density profiles of a bulk and confined fluid, dea) Electronic mail: benjamin.rotenberg@sorbonne-universite.fr fined (for a one-component system of N particles in a volume V ) respectively as the ensemble averages:…”
mentioning
confidence: 99%